Inward Foreign Direct Investment Promotion – A Review of Policy Rationales and Impacts - Robin Gustafsson; Eero Aalto (The Research Institute of the Finnish Economy (ETLA), 2020)
We review the extant research on the government inward foreign direct investment (FDI) policy interventions, concentrating on investment promotion agencies (IPA). Based on the research literature, the review synthesizes inward FDI policy intervention rationales and economic justifications for the intervention, impact evaluations of inward FDI interventions, and current forms and mechanisms of inward FDI promotion. We identify three distinct market failures in attracting FDI justifying public intervention to support FDI: (1) transactional and structural imperfections in the host market to attract FDI of multinational enterprises (MNE); (2) failure to incentivize firms in the home market in attracting inward FDI; and (3) firm constraints in engaging with foreign MNEs. Furthermore, policy interventions are justified due to FDI generates positive spill-over effects to local firms and valuable firm, industry, region, and economy level additionalities from public interventions. Policy interventions facilitating FDIs amplifies spillover-effects on host market firms, especially through increased productivity. Digital infrastructure and platform economy conditions in sectors, reduce transactional and structural imperfections. These advancements also foster more rapid and wider spillover effects. However, they also impose new imperfections in markets with respect to FDI.
Keywords: D83; F21; F23; L15; N70; 330; Foreign direct investment; Investment promotion agencies; Impact evaluation; Policy rationales